2017
DOI: 10.1111/ecc.12660
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on a decision aid for breast cancer screening: Views from women and health professionals

Abstract: This qualitative study evaluates a decision aid that includes the benefits and harms of breast cancer screening and analyses women's perception of the information received and healthcare professionals' perceptions of the convenience of providing it. Seven focus groups of women aged 40-69 years (n = 39) and two groups of healthcare professionals (n = 23) were conducted in Catalonia and the Canary Islands. The focus groups consisted of guided discussions regarding decision-making about breast cancer screening, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…[27][28][29] Our findings were also consistent with prior work finding that women feared underdiagnosis more than overdiagnosis, were suspicious of the underlying reasons for guideline changes, and viewed routine screening as a personal obligation. 30,31 Prior work also shows that women experienced cognitive dissonance when presented with evidence-based mammography information that conflicted with their pre-existing beliefs. 32,33 Our study highlights challenges to offering risk-based screening: the lack of clear communication about guidelines, inconsistent screening recommendations from national bodies and healthcare teams, distrust towards screening guidelines and the healthcare system, and norms promoted by society and personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29] Our findings were also consistent with prior work finding that women feared underdiagnosis more than overdiagnosis, were suspicious of the underlying reasons for guideline changes, and viewed routine screening as a personal obligation. 30,31 Prior work also shows that women experienced cognitive dissonance when presented with evidence-based mammography information that conflicted with their pre-existing beliefs. 32,33 Our study highlights challenges to offering risk-based screening: the lack of clear communication about guidelines, inconsistent screening recommendations from national bodies and healthcare teams, distrust towards screening guidelines and the healthcare system, and norms promoted by society and personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…With a maximum score of 188, the mean ± SD overall assessment score was 132.6 ± 23.8 (range, 85‐172), and there were large variations among the decision aids (Table 1). 5,16‐17,19‐37 The decision aids with the highest overall scores were those described by Hersch et al 24 (172 of 188), Schonberg et al 31 (168 of 188), and Elkin et al 33 (166 of 188). The decision aids with the lowest overall scores were those published by Marshall 25 (95 of 188), Marshall and Adab 26 (94 of 188), and Fuller et al 23 (85 of 188).…”
Section: Resultsmentioning
confidence: 97%
“…Twenty decision aids were in English, 3 of which were also available in another language, including 1 in Chinese, 16 1 in Spanish, 17 and 1 in French 18 . Three decision aids were not available in English, including 1 each in Spanish, 19 German, 20 and French 21 . Fifteen decision aids were available on paper (as a booklet, invitation letter, poster, text, or diagram), 5,17‐19,21‐31 7 were available online, 16,20,32‐36 and 1 available as an audio dialogue (presented with a written version in the published article 37 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent systematic review and meta-analysis assessing the impact of decision aids for screening decisions concluded that decision aids promote an active patient role in decision making 17. A qualitative content analysis study to evaluate women’s views on a decision aid for breast cancer screening using focus groups showed that women preferred shared decision making 49. Our findings differ in that most men reported a practitioner control role in decision making, although few have expressed their preference in this subject but rather shared their experience regarding decision making with their doctors and many evidenced surprise on the possibility of a patient role in decision making.…”
Section: Discussionmentioning
confidence: 99%